Organizational innovation for energy conservation: a case study of Poudre School District - Lueck, Michelle A. M., author; Byrne, Zinta S., author; Cross, Jennifer E., author (Colorado State University. Libraries, 2010)
Since 2000, Poudre School District has built seven green schools and steadily improved the energy performance of all existing school buildings. The Operations Services department has received over 30 awards from local, state, and national agencies for energy conservation and sustainable design. This report provides the results of a case study that examined how Poudre School District adopted innovative practices and became a national leader in high performance buildings. We found that the adoption of sustainable design guidelines and a sustainability ethic was part of a larger organizational transformation that made sustainability the core mission of Operations Services. We describe this change process using an eight-step model that builds on previous research in organizational change; and we discuss the importance of framing the changes to generate broad-based support for sustainability. In addition, we found that Operations Services operates as a "learning organization" in a densely connected network with other public and private organizations.
Keywords: sustainability; high performance buildings; sustainable building design; organizational change; Poudre School District